Exploring the significance of extracellular vesicles: Key players in advancing cancer and possible theranostic tools - Patel, Bhaumik; Gaikwad, Shreyas; Prasad, Sahdeo (Cancer pathogenesis and therapy, 2025)
Metastasis remains a critical challenge in cancer treatment and the leading cause of cancer-related mortality. Ongoing research has demonstrated the key role of extracellular vesicles (EVs) in facilitating communication between distant organs. Cancer cells release a substantial number of EVs that carry distinct cargo molecules, including oncogenic proteins, DNA fragments, and various RNA species. Upon uptake, these cargo molecules profoundly influence the biology of both normal and cancerous cells. This review consolidates the understanding of how EVs promote tumorigenesis by regulating processes such as proliferation, migration, metastasis, angiogenesis, stemness, and immunity. The exploration of EVs as a non-invasive method for cancer detection holds great promise, given that different cancer types exhibit unique protein and RNA signatures that can serve as valuable biomarkers for early diagnosis. Furthermore, growing interest exists in the potential bioengineering EVs for use as prospective therapeutic tools for cancer treatment. [Display omitted] •Extracellular vesicles (EVs) play pivotal roles in cancer from inception through all phases of development.•EV-mediated signaling profoundly influences the tumor microenvironment (TME), fostering immune evasion.•EV-based liquid biopsies are promising when biopsy sampling is challenging.•Engineered EVs show potential for targeting tumors more precisely.